Pengaruh rasio keuangan sebagai salah satu alat untuk memprediksi perubahan laba pada perusahaan indeks kompas 100 tahun 2011-2012 - Sari Ramadhani; Azwir Nasir; Al-azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to demonstrate empirically the influence of the current ratio, debt to equity ratio, net profit margin, return on equity and total asset turnover against the company predicted earnings change index Compass 100 Years 2011-2012.The data used in this study is a data company financial statements Compass 100 index listed in the Indonesia Stock Exchange during 2011-2012. Sampling technique is purposive sampling method sampling with particular consideration. The analysis technique used in this study is the technique of multiple linear regression analysis.The results of this study stated that the partial test can be concluded that the ROE has a significant effect on earnings growth. It can be seen from the t value (3,147)> t table ((1973) so that Hi Ho rejected and accepted. Likewise with DER that can be seen from the t value (-4140)> t table ((1973), so that Ho Hi rejected and accepted. while CR does not have a significant effect on earnings growth, it can be seen from the t (-0.375) <t table (1.973), then NPM with t (1,152) <t table (1.973) then TATTOOS with t count (-0.887) <t table (1.973), the Hi Ho accepted and rejected. Levels coefficient of determination R2 = 0.124 is owned by. this means that about 12.4% of banking profit growth is influenced by the variable current ratio, net profit margin ratio, return on equity, total asset turnover and debt-to-equity ratio, the profit growth. while about 87.6% influenced by other variables.Keywords: Current Ratio, Debt to Equity Ratio, Net Profit Margin, Return on Equity and Total Assets Turn Over, Predictive Earnings